Impact of anxiety on the post-discharge outcomes of patients discharged from the hospital after an acute coronary syndrome. (1st March 2019) - Tran, Hoang; Byatt, Nancy; Erskine, Nathaniel; Lessard, Darleen; Devereaux, Randolph S.; Saczynski, Jane; Kiefe, Catarina; Goldberg, Robert
Abstract: Background: Symptoms of anxiety are highly prevalent among survivors of an acute coronary syndrome (ACS), but do not necessarily indicate an anxiety disorder. The extent to which symptoms of anxiety or a diagnosis of this condition impacts hospital readmission and post-discharge mortality among patients with an ACS remains unclear. Methods: We used data from 1909 patients discharged from six hospitals in Massachusetts and Georgia after an ACS. Moderate/severe symptoms of anxiety were defined based on responses to a Generalized Anxiety Disorder questionnaire during the patient's index hospitalization. The diagnosis of an anxiety disorder was based on review of hospital medical records. Multivariable adjusted Poisson regression and Cox proportional-hazards models were used to estimate the risk of 30-day hospital readmissions and 2-year total mortality. Results: The mean age of the study population was 61 years, two thirds were men, and 78% were non-Hispanic whites. In this population, 10.4% had a documented diagnosis of an anxiety disorder, 18.8% had moderate/severe symptoms of anxiety, and 70.8% had neither a diagnosis nor symptoms of anxiety. Neither a diagnosis of an anxiety disorder nor symptoms of anxiety were associated with 30-day all-cause or cardiovascular-related rehospitalizations. Patients with an anxiety disorder (multivariable adjusted HR = 1.95, 95%CI = 1.11–3.42) were at greatest risk for dying during the 2-year follow-up period. Conclusions: We identified patients with an anxiety disorder as being at greater risk for dying after hospital discharge for an ACS. Interventions may be more appropriately targeted to those with a history of, rather than acute symptoms of, anxiety. Highlights: Symptoms of anxiety are prevalent among hospital survivors of an acute coronary syndrome (ACS) Anxiety symptoms or established anxiety disorder were not associated with 30 day all-cause or CVD-related rehospitalization Established anxiety disorder, but not anxiety symptoms, were associated with higher mortality risk over 2 years of follow-up